2008
DOI: 10.1007/s10822-008-9229-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation study of PTP1B with allosteric inhibitor and its application in receptor based pharmacophore modeling

Abstract: Allosteric inhibition of protein tyrosine phosphatase 1B (PTP1B), has paved a new path to design specific inhibitors for PTP1B, which is an important drug target for the treatment of type II diabetes and obesity. The PTP1B1-282-allosteric inhibitor complex crystal structure lacks alpha7 (287-298) and moreover there is no available 3D structure of PTP1B1-298 in open form. As the interaction between alpha7 and alpha6-alpha3 helices plays a crucial role in allosteric inhibition, alpha7 was modeled to the PTP1B1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The second idea is that allosteric networks and control are conserved features in protein families (32). The fundamental question of whether site-to-site communication is conserved is one of therapeutic relevance, as allostery is a major consideration in drug design not only for the human Kinesin-5 proteins but for other protein families as well (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The second idea is that allosteric networks and control are conserved features in protein families (32). The fundamental question of whether site-to-site communication is conserved is one of therapeutic relevance, as allostery is a major consideration in drug design not only for the human Kinesin-5 proteins but for other protein families as well (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Several X-ray crystal structure analyses and computational simulations recently revealed the binding sites of allosteric inhibitors and the inhibitory mechanisms in which a small molecule binds to allosteric sites and stabilizes the conformation associated with the inactive state of PTP1B. [37][38][39][40][41][42][43][44] Based on the molecular similarities between our compound 18K and an allosteric inhibitor bound to PTP1B (Fig. 2a), we constructed a structural model of the 18K-PTP1B complex by molecular alignment of the compounds, followed by validation and refinement of the structure obtained using a molecular dynamic (MD) simulation.…”
Section: Resultsmentioning
confidence: 99%
“…This allosteric site makes these inhibitors highly selective for PTP1B. The allosteric inhibitor may act by stabilizing the conformation that precludes the closure of the WPD loop (Kamerlin et al, 2007;Bharatham et al, 2008). Bialy and Waldmann (2005) reported that noncompetitive or allosteric inhibitors might oxidize the catalytic cysteine (Cys215).…”
Section: Discussionmentioning
confidence: 99%